Globalización, capitalismo financiero y responsabilidad social empresarial: tensiones estructurales (2014)
Globalization and financial capitalism keep a synergy in a global context whose problems such as environmental degradation, social inequity, economic crises and corruption are intensified. Corporate Social Responsibility emerges as a mechanism that seeks to mitigate some of these problems, although its effectiveness and impact today are challenged. The system which globalization, financial capitalism and social responsibility are a part of, is currently facing a number of structural tensions that contribute to the analysis, understanding and solving of the mentioned problems. This paper identifies and analyzes four of the aforementioned structural tensions.